Integration of Technology During the COVID-19 Pandemic: Experience, Challenges and Needs of Thai EFL Teachers - Boonmoh, Atipat; Jumpakate, Thidaporn; Saengmanee, Sawitree; Rungkaew, Titirut (rEFLections, 2022)
COVID-19 has led to an abrupt change from traditional classrooms and face-to-face learning to emergency online learning. The outbreak of COVID-19 in Thailand in early 2021 forced school closures and increased online learning. Students were not given a choice but to study at home. This study reports on the experience and challenges of language teachers from Thai universities who taught in emergency online settings. It examined their needs for future professional development courses. An online survey was completed by 120 EFL teachers from 52 universities across Thailand. Of these, six also participated in an online semi-structured interview. The survey findings revealed that 108 teachers (90%) had never taught online previously. ZOOM and Google Meet were among the most popular virtual meeting platforms. Support from their universities, as reported in the survey, included providing basic information and communications technology (ICT) skills workshops (75.8%), and providing workshops on integrating technology into classrooms (51.7%). The main challenges relating to online learning are the absence of a physical setting and a lack of interaction between students and teachers. In terms of future professional development needs, the data indicated that most teachers do not need courses in fundamental ICT skills or courses that expose them to a range of online technology tools. They do, however, need additional approaches to enhance their online teaching abilities, as well as certain teaching techniques to enable them to apply their pedagogical expertise while using specific technological tools or applications with which they are familiar. On the basis of these findings, pedagogical implications are discussed.